2019
DOI: 10.1002/2211-5463.12729
|View full text |Cite
|
Sign up to set email alerts
|

5‐ALA/SFC enhances HO‐1 expression through the MAPK/Nrf2 antioxidant pathway and attenuates murine tubular epithelial cell apoptosis

Abstract: Cyclosporin A (CsA) is a common immunosuppressant, but its use is limited as it can cause chronic kidney injury. Oxidative stress and apoptosis play a key role in CsA‐induced nephrotoxicity. This study investigated the protective effect of 5‐aminolevulinic acid and iron (5‐ALA/SFC) on CsA‐induced injury in murine proximal tubular epithelial cells (mProx24). 5‐ALA/SFC significantly inhibited apoptosis in CsA‐treated mProx24 cells with increases in heme oxygenase (HO)‐1, nuclear factor E2‐related factor 2 (Nrf2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…protect kidneys from acute injury [15,16]. Moreover, both in vivo and in vitro studies show that 5-ALA can induce heme oxygenase-1 (HO-1) expression in kidney cells [17,18].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…protect kidneys from acute injury [15,16]. Moreover, both in vivo and in vitro studies show that 5-ALA can induce heme oxygenase-1 (HO-1) expression in kidney cells [17,18].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Glycine, a non-essential amino acid, combines with succinyl-CoA to form 5-ALA in the presence of 5-ALA synthase as part of the heme biosynthetic pathway in animals [ 14 ]. 5-ALA can reduce nephrotoxicity and apoptosis in murine tubular epithelial cells and can protect kidneys from acute injury [ 15 , 16 ]. Moreover, both in vivo and in vitro studies show that 5-ALA can induce heme oxygenase-1 (HO-1) expression in kidney cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 was markedly upregulated after IRI and its expression was even 1.32-fold higher in mice treated with rapamycin [ 82 ]. Moreover, HO-1 induction may have a beneficial effect on cyclosporine-mediated toxicity, through a reduction of fibrosis of proximal tubules and renal apoptosis [ 83 , 84 , 85 ]. Taken together, these studies suggest that chronic immunosuppression is responsible for cellular stress at kidney level and this may upregulate the expression of HO-1.…”
Section: Acute and Chronic Rejection And Immunosuppressionmentioning
confidence: 99%
“…A recent study by our group found that 5-ALA could reduce heat stress-mediated ER stress-induced apoptosis of bovine MECs [ 13 ]. 5-ALA also effectively inhibits apoptosis in response to OxS and other stressors [ 14 , 15 , 16 , 17 ]. Therefore, 5-ALA has the potential to protect bovine MECs, thereby facilitating an optimum amount of milk production.…”
Section: Introductionmentioning
confidence: 99%